Analisis Penggunaan Resistance Sebagai Peredam Arus Kejut Aki 12V Pada Battery Management System(BMS): Electric Vehicle - rizki alhidayat (Jurnal Qua Teknika, 2022)
The development of electric car technology is currently increasing a lot of progress. Thisrepresents an electric car is one alternative to future vehicles using battery energy to move it. But nowthere are many weaknesses in special electric cars in Indonesia. One of them is battery charging that canbe said to be ineffective. When the battery in this electric car consists of 4 12V batteries, which areequipped with 48V in the charging process. The type of battery used is Battery Sealed Lead Acid wherethe battery is a sulfuric acid electrolyte rechargeable battery that cannot be stacked because this batterycan be coagulated (thickened). In this system a boost converter is used to stabilize the voltage from thePLN that will enter through the charger. Then in menitoring the charger, there needs to be an Internetsystem Object or an abbreviation of IoT for convenience whether the battery is full or not. And for themicrocontroller used is ESP32. In addition to this the IoT system can also calculate the efficiency of thecharger for each charging. Related cell phone owners can monitor the battery via a smartphone or laptopconnected to the internet.